Method for tribological experiment to study scuffing initiation on AISI 52100 steel and hard ceramic coatings. (August 2021) - Jacques, Kelly; Murthy, Nikhil; Dixit, Satish; Berman, Diana; Berkebile, Stephen
Abstract: Though many models of wear have been proposed, the design of the lab-scale experimental procedures to reproduce and characterize a particular wear regime, scuffing, has been difficult to generalize and more limited in scope. In this study, we used a high-frequency reciprocating tribometer to determine a set of tribological experimental parameters that instigate material scuffing and yield reliable and repeatable results by varying grinding lay orientation, temperature, counter body material, substrate hardness, contact load, stroke length, and frequency. The onset of scuffing in through-hardened 52100 steel substrates lubricated with low viscosity fuels was most repeatable with a perpendicular grinding lay and alumina counterface, while no effect was observed with substrate temperature. The experimental method using a load progression from 1 N to 18 N was then used on several protective coatings to determine their effectiveness in inhibiting scuffing initiation. Highlights: Experimental method for scuffing initiation of various materials and fuel lubricants is designed. Tungsten carbide coatings protect steel from scuffing in low-viscosity fuel. Scuffing behavior of steel and ceramic coatings in fuel lubrication is compared.